Hubungan Siklus Menstruasi Terhadap Perfomance Atlet Atletik Lompat Jauh Putri PPLP Provinsi Bengkulu: The Relationship of Menstrual Cycle to Performance of Female Long Jump Athletic Athletes PPLP Bengkulu Province - Rio Eben Ezer Pasaribu; Yarmani; Septian Raibowo (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Abstract The problem in this study is that female long jump athletes often feel a decrease in performance during menstruation, this study examines the relationship between the menstrual cycle and the performance of female long jump athletes. While the purpose of the study was to determine whether or not there was a relationship between the menstrual cycle and the performance of female long jump athletes. This research method is quantitative. The population of this study were 20 female long jump athletes from PPLP Bengkulu Province. The data obtained by the results of the study with the correlation test obtained the rᵪᵧ= 0.912 >  0.444. It can be concluded that there is a relationship between the menstrual cycle and the performance of female long jump athletes in PPLP Bengkulu Province.   Keywords: Athletics, Long Jump, Menstrual Cycle,  Performance